Dwarf gynes in Nannotrigona testaceicornis (Apidae, Meliponinae, Trigonini). Behaviour, exocrine gland morphology and reproductive status - Imperatriz-Fonseca, V. L.; Cruz-Landim, Carminda da [UNESP]; Moraes, R. L. M. Silva de [UNESP] (Springer Nature, 1997)
The behaviour and morphology of dwarf gynes produced in worker-sized cells of normal colonies in Nannotrigona testaceicornis (Meliponinae, Trigonini) were studied. The behaviour of these dwarf virgin queens was the same as observed for normal Trigonine gynes. The glandular equipment is also the same: Dufour glands, fat bodies and spermathecae are present. Despite these similarities, their ovaries are different. The functional significance of dwarf gynes is unknown, but may be a basis for an alternative reproductive strategy.
Keywords: Dwarf gynes; Larval food; Nannotrigona testaceicornis; Reproductive strategies; Stingless bees; Trigonini; dwarf gyne; dwarf virgin queen; morphology; reproductive status; reproductive strategy; animal behavior; bacterial colonization; bee; body composition; histopathology; larval development; reproduction; Apidae; Hymenoptera